Development of an updated, standardized, patient-centered outcome set for lung cancer. (November 2022) - de Rooij, Belle H.; van den Hurk, Corina; Smaardijk, Veerle; Fernandez-Ortega, Paz; Navarro-Martin, Arturo; Barberio, Lidia; Guckenberger, Matthias; Schmid, Severin; Walraven, Iris; Vallow, Susan; Kotsi, Christina; Preusser, Matthias; et al.
Highlights: Since the development of the International Consortium for Health Outcomes Measurements (ICHOM) lung cancer outcome set in 2016, there have been significant advances in the treatment of lung cancer. The present study describes an updated, enriched, core outcome set (COS) to capture the patient perspective of the impact of lung cancer and (novel) treatments using a combination of patient-reported outcome (PRO) instruments and clinical data. We used a consensus-based Delphi approach in a large international, multidisciplinary group of 146 stakeholders. The final COS includes 64 outcomes, including case-mix factors, PROs related to health-related quality of life and clinical outcomes. The COS will be implemented in clinical centres across Europe as part of the Health Outcomes Observatory (H2O) IMI project which is designed to drive value-based healthcare in Europe to optimize care delivery. Abstract: Background: In 2016, the International Consortium for Health Outcomes Measurement (ICHOM) defined an international consensus recommendation of the most important outcomes for lung cancer patients. The European Health Outcomes Observatory (H2O) initiative aimed to develop an updated patient-centered core outcome set (COS) for lung cancer, to capture the patient perspective of the impact of lung cancer and (novel) treatments using a combination of patient-reported outcome (PRO) instruments and clinical data as a means to drive value-based health-care. Material and methods: An international, expert team of patient representatives, multidisciplinary healthcare professionals, academic researchers and pharmaceutical industry representatives (n = 17) reviewed potential outcomes generated through literature review. A broader group of patients/patient representatives (n = 31), healthcare professionals / academic researchers (n = 83), pharmaceutical industry representatives (n = 26), and health authority representatives (n = 6) participated in a Delphi study. In two survey rounds, participants scored the relevance of outcomes from a preliminary list. The threshold for consensus was defined as ≥ 70 % of participants scoring an outcome as 'highly relevant'. In concluding consensus-meeting rounds, the expert multidisciplinary team finalized the COS. Results: The preliminary list defined by the core group consisted of 102 outcomes and was prioritized in the Delphi procedure to 64. The final lung cancer COS includes: 1) case-mix factors (n = 27); 2) PROs related to health-related quality of life (HRQoL) (n = 25); 3) clinical outcomes (n = 12). Patient-reported symptoms beyond domains included in the ICHOM lung cancer set in 2016 were insomnia, nausea, vomiting, anxiety, depression, lack of appetite, gastric problems, constipation, diarrhoea, dysphagia, and haemoptysis. Conclusions: We will implement the lung cancer COS in Europe within the H2O initiative by collecting the outcomes through a combination of clinician-reported measures and PRO measures. The COS will support the adoption and reporting of lung cancer measures in a standardized way across Europe and empower patients with lung cancer to better manage their health care.